Management of ankle injuries in professional basketball players: Prevalence and rehabilitation - Moore, M. Lane (Orthop Rev (Pavia), 2021)
Basketball is a popular internationally played sport. With the physical requirements the game has on athletes, players are at risk of injury. Ankle injuries are the most common injury type suffered by basketball players. In this comprehensive review, we present an analysis and overview of the most common ankle injuries among basketball players, including sprains, fractures, impingement, and Achilles tendon pathology. The review includes treatment modalities for such injuries. More research is warranted regarding prevention strategies.